VD_FINDINFO Décision / 2022 / 325 vom 12. April 2022 - VD Tribunal cantonal (2022)
DIFFAMATION, CALOMNIE, NON-LIEU, ADMISSION DE LA DEMANDE, TIERS, SAUVEGARDE DU SECRET | 173 ch. 1 CP, 173 ch. 2 CP, 174 CP, 310 CPP (CH)